2020
DOI: 10.3390/electronics9122047
|View full text |Cite
|
Sign up to set email alerts
|

Circuit Model and Analysis of Molded Case Circuit Breaker Interruption Phenomenon

Abstract: There are complex physical phenomena for the interpretation of a molded case circuit breaker (MCCB) in a distribution system. Most of the studies of MCCB interruption phenomena were conducted with numerical analysis and experiments. This traditional approach may help improve the performance of the MCCB itself, but it is difficult to find connectivity with other systems. In this paper, the circuit model is proposed and the interruption phenomenon of MCCB is analyzed. The interruption of the MCCB is divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…When one CLL curve has been developed and tested, the CLL curves for other conditions can be derived based on the existing one. By performing numerical analysis on the data of the CLL assessments in Sections 3 and 4, it was found that a new CLL curve could be developed according to (7): CLL New = P base P New × CLL base (7) In (7), CLL base and P base are the existing CLL point and its related power delivery level, respectively, and CLL new and P new are the new CLL point and its related power delivery level, respectively. When the effective length of the ZCB is measured and calculated for the base condition, all the other effective length curves can be generated conveniently with (7).…”
Section: Verification and Generation Of Cll Curvesmentioning
confidence: 99%
See 1 more Smart Citation
“…When one CLL curve has been developed and tested, the CLL curves for other conditions can be derived based on the existing one. By performing numerical analysis on the data of the CLL assessments in Sections 3 and 4, it was found that a new CLL curve could be developed according to (7): CLL New = P base P New × CLL base (7) In (7), CLL base and P base are the existing CLL point and its related power delivery level, respectively, and CLL new and P new are the new CLL point and its related power delivery level, respectively. When the effective length of the ZCB is measured and calculated for the base condition, all the other effective length curves can be generated conveniently with (7).…”
Section: Verification and Generation Of Cll Curvesmentioning
confidence: 99%
“…The quenching of such an arc is the most significant concern since it increases the cost of maintenance and reduces the lifespan of the breaker [4][5][6]. A circuit model of a molded-case circuit breaker (MCCB) is proposed and the interruption phenomenon of the MCCB is analyzed in [7]. The dielectric recovery strength of a low-voltage MCCB is improved by changing the splitter plate [8].…”
Section: Introduction 1dc Network Development and Protection Solutionsmentioning
confidence: 99%
“…In the future, when the full DC power demand is achieved, many MCs are expected to be driven by DC power owing to the lack of sufficient alternating current (AC) power [4,5]. Moreover, in the existing AC networks, the use of DC-type MC is increasing to prevent the malfunction of the surrounding electronic devices owing to arcs generated when the MC is turned off [6,7]. For this reason, studies on the electromagnetic effect occurring in DC excitation-type electronic contactors are also being actively conducted [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The currently proposed DCCBs can be mainly divided into three types: the mechanical DCCB, the solid-state DCCB, and the hybrid DCCB [6][7][8][9]. Since the solid-state DCCB has extremely high power losses during normal operation, it is more appropriate to be adopted in the low-and medium-voltage dc systems [10].…”
Section: Introductionmentioning
confidence: 99%